Wine Industry Campaign Contributions and Wine Excise Taxes: Evidence from U.S. States. (26th April 2018) - Pokharel, Shree B.
Abstract: Given the growing importance of the wine industry in the United States, wine special interests are on the rise. Data shows that campaign contributions from the wine industry to officials running for state offices have increased over time. Given this reality, one can expect wine excise tax to remain low in states that receive higher campaign contributions. In addition, there are theoretical and empirical reasons to believe that these tax rates are interdependent based on Tiebout competition and yardstick competition. Based on this reasoning, one can hypothesize wine excise tax rates to be spatially dependent. In this study, I test this hypothesis using state-level campaign contributions data from the National Institute on Money in State Politics and Distilled Spirits Council of the United States, Inc. and find that there is strong statistical evidence of spatial dependence between state wine excise tax rates. (JEL Classifications: C12, C23, H71)